0117 Two-Year Memory Change is Associated with Sleep Disorders in a Survey of Older Adults. (25th May 2022) - Wills, Chloe; Mason, Brooke; Tubbs, Andrew; Killgore, William; Grandner, Michael
Abstract: Introduction: Insufficient sleep and sleep disorders have been previously associated with worse cognitive outcomes, such as worse memory performance. This analysis aims to assess the relationship between diagnosed sleep disorder and memory change over a period of two years. Methods: N=17, 156 older adults residing in the United States were assessed using the Health and Retirement Survey (Core) in 2018, with additional variables obtained in the previous wave (2016 on the same participants). Those who reported no sleep disorder in either wave were categorized as "no sleep disorder, " and they were compared to those who reported a sleep disorder in both waves ("sustained sleep disorder") or one wave but not the other ("new sleep disorder" or "remitted sleep disorder." Memory change was assessed using a survey item asking if the respondent's memory was "worse", "better", or "the same" as compared to two years prior. Multinomial logistic regression was used to assess the relationship between these variables, and results were adjusted for sex, age, race, ethnicity, and depression. Results: In adjusted results, those who reported that their memory improved were 124% (OR=2.24; 95%CI[1.51, 3.31]; p<0.001) more likely to have a sleep disorder that was remitted in the past 2 years. Those who reported that their memory worsened were 103% more likely to have a new sleep disorder (OR=2.03; 95%CI[1.65, 2.50]; p<0.001), and 58% more likely to have a sustained sleep disorder (OR=1.58; 95%CI[1.40, 1.77]; p<0.001). Interestingly, those whose memory worsened were also 39% more likely to have a remitted sleep disorder (OR=1.35; 95%CI[1.10, 1.77]; p=0.006). Conclusion: In older adults, there is a relationship between change in memory function and sleep disorders, such that improved memory is associated with improved sleep and worsened memory is associated with worse sleep or sustained sleep problems. Unfortunately, the specific sleep disorders associated were not reported. Future work should examine these effects in terms of specific sleep disorders, additional effect modifiers/covariates, and the role of sleep health in improving memory function. Support (If Any): The HRS (Health and Retirement Study) is sponsored by the National Institute on Aging (grant number NIA U01AG009740) and is conducted by the University of Michigan.